Bimbingan Teknis untuk Meningkatkan Kompetensi Guru Madrasah pada Sekolah Ramah Anak dalam Menyusun Strategi Efektif untuk Melatih Siswa dalam Kompetisi Sains Madrasah - Ilmianih, Rizki; D, Darsikin; Saehana, Sahrul; M, Muslimin; S, Syamsu; Sani, Nurul Kami; Khuzaimah, Andi Ulfah (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
This community service activity was carried out as an effort to improve the competence of madrasah teachers in developing science learning that is integrated with the values of the Qur'an and Hadith, as well as encouraging the creation of a child-friendly learning environment. The background of this activity is based on the fact that teachers still find it difficult to develop learning strategies that are able to connect scientific concepts with religious teachings, resulting in low student readiness to face academic competition at the madrasah level. The main objective of this program is to provide technical guidance to teachers so that they are more skilled in designing integrated learning, while also increasing student readiness to face national science competitions. This activity was carried out at MTsN 2 Palu, involving eight science teachers and Al-Qur'an and Hadith teachers, as well as 22 students in grades VII to IX. This activity was designed in five stages, namely needs analysis, development of integrated science modules, focused group discussions, teacher and student mentoring, and evaluation. The developed module contains five main science themes integrated with verses from the Qur'an and Hadith, and is used as the primary tool in learning. The results of the activity show that teachers have improved their skills in developing science and religion-based learning strategies, while students have benefited from increased motivation, confidence, and ability.